EFEKTIVITAS PROGRAM PENINGKATAN PENGHIDUPAN MASYARAKAT BERBASIS KOMUNITAS (PPMK) DALAM MENINGKATKAN PENDAPATAN DI LEMBAGA KESWADAYAAN MASYARAKAT (LKM) MARGODADI JAYA KOTA METRO - Indah Ayu Dianti; Tubagus Hasanuddin; Begem Viantimala (Lampung University, 2018)
This study aims to find out the implementation of PPMK programme in Margodadi Subdistrict Metro City, to find out whether the PPMK programme has been effective in improving the income of KSM members in Metro City, and to find out the factors related to the effectiveness of PPMK Programme in Metro City. The location of this study was chosen purposively in Non-Governmental Organization (NGO) Margodadi Sub District, South Metro District, Metro City. The respondents of this research are 25 members of Kelompok Swadaya Masyarakat (KSM) who got capital loans in PPMK Programme. Data of this research was collected in August-September 2016. The research method used case method in which data was analyzed by descriptive and tabulation analysis to test the hypothesists. The results of the research showed that the implementation of PPMK Programme had been running well . PPMK Program was effective on improving the income of KSM members, and the factors that related to the effectiveness of PPMK Programme were human resource quality, sosial capital condition, and finance resource quality.Key words: effectiveness, LKM, PPMK Programme